Valorization of Fibrous Waste for the Wastewater Discoloration - Ouslimani, N.; Zrari, F.; Abadlia, M.T.; Benabed, H. (Asian Journal of Chemistry, 2013)
The aim of this work is the discoloration of the water dyeing unit DBK by waste cotton fiber as adsorbents. The dyes used are reactive dyes According to the results, it is found that the rate increases with increasing fading of the fiber mass (the adsorbent) and the contact time with the colored solution and the stirring time.